2016
DOI: 10.1093/infdis/jiw014
|View full text |Cite
|
Sign up to set email alerts
|

Within-Host Heterogeneity ofMycobacterium tuberculosisInfection Is Associated With Poor Early Treatment Response: A Prospective Cohort Study

Abstract: The clinical management of tuberculosis is a major challenge in southern Africa. The prevalence of within-host genetically heterogeneous Mycobacterium tuberculosis infection and its effect on treatment response are not well understood. We enrolled 500 patients with tuberculosis in KwaZulu-Natal and followed them through 2 months of treatment. Using mycobacterial interspersed repetitive units-variable number of tandem repeats genotyping to identify mycobacterial heterogeneity, we report the prevalence and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 14 publications
4
45
1
Order By: Relevance
“…In contrast, Cohen et al . showed that the negative effect of polyclonal infections on the response to early treatment appeared to be independent of a relationship with drug resistance in TB patients in KwaZulu-Natal, South Africa15. This difference may be related to the follow-up period; which ended at six and two months in our and Cohen’s study, respectively.…”
Section: Discussionmentioning
confidence: 46%
“…In contrast, Cohen et al . showed that the negative effect of polyclonal infections on the response to early treatment appeared to be independent of a relationship with drug resistance in TB patients in KwaZulu-Natal, South Africa15. This difference may be related to the follow-up period; which ended at six and two months in our and Cohen’s study, respectively.…”
Section: Discussionmentioning
confidence: 46%
“…Examining the bases mapped to each site using per-base binomial testing (see Methods) shows sample-C from patient-1 contains multiple mixed positions (M-sites) at the sites differing between A and B. This kind of within-patient heterogeneity, which is reported to be associated with impaired treatment response, 10, 13, 14 is not evident using standard methods of consensus base calling, using which C appears identical to (that is, has a zero pairwise SNV distance from) sample A. Consequently, we decided to develop automated methods detecting mixed TB infection using our routinely sequenced data.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, although we observed microvariation to be more commonly detected in lineages 1-3 than in the most common UK lineage-4, the biological basis for this needs further study. Thirdly, although mixed infection has been associated with delayed response to therapy in high incidence settings, 10 we were unable to determine whether this occurs in the UK as the UK’s national TB surveillance scheme does not collect suitable data on treatment response; it records only rates of treatment completion within 12 months of diagnosis, or within 24 months for cases with rifampicin or multidrug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations